Occupational stress among the information technology (IT) professionals in selected companies in the Klang Valley - Ng, Siew Foen (1999)
Stress in the workplace is becoming the most common complaint of the late 20th century employee. It is a costly, pervasive phenomenon in work organizations and many studies have been carried out in the west to investigate this area of human concern. The objective of this study is to examine the occupational stress level of the IT professionals in selected companies an d factors that cause occupational stress among them. It was hypothesize d that there were significant differences between occupational stress level and the demographic variables of the IT professionals. The demographic variables involved were 1) age, 2) sex, 3) education background, 4) work department, and 5) annual gross salary. The population in this study consists of the IT professionals from 5 companies in the Klang Valley. Questionnaires using six-point Likert-type scales were used to measure the variables. The data collected were analysed using the SPSS. Descriptive statistics were used to describe the demographic profile of samples. Independent t-tests were employed to compare the significant differences in the level of occupational stress for gender. The ANOVA was used for hypotheses testing the significance differences in the level of occupational stress for other demographic variables.